Penggunaan dan Analisis Modal Verbs Kunci (Should, Will, Would, Can, Could, May, Might, Must) dalam Bahasa Inggris - Muhlisin; Muhammad Ilham; Rahmadiyanti; As-Syifa Salsabila; Mila Erliana; Dewo Prasetiyo; Ahmad Rasyid (INDO PUBLISHING, 2025)
This research aims to provide a comprehensive analysis of the nine key modal auxiliary verbs in the English language, as presented in the study titled